PENGARUH AUDIT FEE, PENGALAMAN AUDIT, DAN SKEPTISME PROFESIONAL TERHADAP KUALITAS AUDIT DENGAN INDEPENDENSI SEBAGAI VARIABEL MODERASI (Survei pada KAP di Jawa Tengah dan DIY) - Ana, Liya Wahyu; Puji Astuti, Dewi Saptantinah; Kristianto, Djoko (Universitas Slamet Riyadi, 2020)
Audit quality is very important because the financial statements that have been audited by public accountants are more reliable than the fairness of the financial statements that are not or have not been audited.0The purpose of this study was0to analyze the significance of the effect of audit fees, auditor experience, and professional skepticism on audit quality with independence0as a moderating variable. .This0study took0a sample of 87 respondents from all auditors in Central Java and Yogyakarta, using00accidental sampling.0Data collection methods: questionnairesâ€and documentation. The0data analysis technique0is descriptive statistics, validity0test, reliability0test, classic0assumption test, multiple linear regression test, and interaction test. The0results of the study concluded that0audit fees, auditor experience, and professional skepticism had a positive and0significant effect on audit0quality. And Independence moderates the relationship between audit fees, auditor experience, and professional skepticism about audit quality.